KONSEP ECOLOGICAL CITY DALAM KERANGKA KONSEP EKOLOGI KOTA DAN KOTA BERKELANJUTAN - Enni Lindia Mayona (Jurnal Planologi, 2021)
ABSTRACTCity growth that continues to occur is unavoidable and affects the environment, so an ecological approach is needed to overcome it. One of the city concepts that has developed along with the historical perspective of urban ecology is the ecological city (ecocity). In the development of ecocity in several countries that carry the theme of sustainability city, both practice and concept do not explain the "process" to achieve the city's environmental sustainability goals. The purpose of this paper is to examine the theoretical position of the ecological city concept within the framework of urban ecology and sustainable cities. The method used is a literature review based on the development of the concept of ecocity, urban ecology and sustainable city. Based on the results of the study, it shows that in the urban ecology approach, ecocity can be concluded as a concept that balances the city's metabolism (ecology of cities) through the independence of the structure and function of the ecosystem where humans play a role in determining the process of adaptation and urban development. In the concept of a sustainable city along with the development of eco-form which represents ecological considerations in urban and community spaces, it shows that urban form is one of the elements that can be intervened in achieving sustainable city goals. Ecocity as an eco-form is in the challenge of conflict between aspects of the social environment where the conflict that occurs has shifted from development conflict to green conflict in a sustainable prism. The results of the study show that in the process of managing an environmentally sound city environment (ecocity) it is necessary to consider the integration of humans as social aspects in interaction with ecosystems (social-ecology) in city metabolism as the basis for providing ecosystem services and urban green infrastructure. Keywords: ecological city, city ecology, sustainable city, city metabolism ABSTRAKPertumbuhan kota yang terus terjadi tidak dapat dihindari dan berpengaruh terhadap lingkungan, sehingga dibutuhkan pendekatan ekologi untuk mengatasinya. Salah satu konsep kota yang berkembang seiring dengan perspektif sejarah ekologi kota (urban ecology) adalah ecological city (ecocity). Pada perkembangan ecocity di beberapa negara yang mengusung tema kota keberlanjutan baik praktek maupun konsep tidak menjelaskan “proses” untuk mencapai tujuan keberlanjutan lingkungan kota tersebut. Tujuan makalah ini adalah mengkaji kedudukan secara teoritis konsep ecological city dalam kerangka ekologi kota (urban ecology) dan kota berkelanjutan (sustainability city).  Metode yang digunakan adalah review literatur berdasarkan perkembangan konsep ecocity, urban ecology dan sustainable city. Berdasarkan hasil kajian menunjukkan dalam pendekatan urban ecology, ecocity dapat disimpulkan sebagai konsep yang menyeimbangkan metabolisme kota (ecology of cities) melalui kemandirian struktur dan fungsi ekosistem  dimana manusia berperan di dalam menentukan proses adaptasi dan perkembangan kota. Dalam konsep kota berkelanjutan seiring dengan perkembangan eco-form yang merepresentasikan pertimbangan ekologi di dalam ruang kota dan komunitas menunjukkan bentuk kota (urban form) merupakan salah satu unsur yang dapat diintervensi  di dalam mencapai tujuan kota yang berkelanjutan. Ecocity sebagai eco-form berada di dalam tantangan konflik antara aspek lingkungan sosial dimana konflik yang terjadi mengalami pergeseran dari development conflict ke arah green conflict di dalam prisma berkelanjutan. Hasil kajian menunjukkan di dalam proses pengelolaan lingkungan kota yang berwawasan lingkungan (ecocity) perlu mempertimbangkan integrasi manusia sebagai aspek sosial dalam interaksi dengan ekosistem (sosial-ekologi) di dalam metabolisme kota sebagai dasar di dalam penyediaan ecosystem services dan infrastruktur hijau perkotaan.Kata Kunci : ecological city, ekologi kota, kota berkelanjutan, metabolisme kota